Progressive multifocal leukoencephalopathy in a patient with relapsing multiple sclerosis treated with ocrelizumab: A case report - Puig‐Casadevall, Marc; Álvarez‐Bravo, Gary; Varela, Ana Quiroga; Robles‐Cedeño, René; Sànchez Cirera, Laura; Miguela, Albert; Laguillo, Gemma; Montalban, Xavier; Hauser, Stephen L.; Ramió‐Torrentà, Lluis (European journal of neurology, 2023)
IntroductionProgressive multifocal leukoencephalopathy is a rare but often fatal complication of some multiple sclerosis treatments. Although it has mainly been associated with natalizumab treatment, its appearance with other immunosuppressive therapies has also been reported.AimsThe aim of this case report is to describe the development of progressive multifocal encephalopathy in a patient with relapsing–remitting multiple sclerosis treated with ocrelizumab without previous use of natalizumab.ConclusionsA summary of the presentation and disease course is provided, presented in the context of the current literature and likely pathophysiology.